Open Access—Are the Barriers to Change Receding? - Bo-Christer Björk (Publications, 2013)
The move from subscription only publishing of scholarly articles to open access has been much slower than previously anticipated by many Open Access (OA) advocates. Despite the many advantages that OA offers, this particular branch of E-commerce imposes several formidable barriers to change. A framework conceptualizing these barriers that was developed over a decade ago was revisited to see if the significance of these barriers has changed. Nowadays, building the IT infrastructure, support from indexing services and finding a sustainable business model are no longer important barriers. For gold OA publishing the academic reward system is still a major obstacle, whereas more marketing and critical mass is needed for both gold OA and green OA. Green OA self-archiving is still also strongly affected by what subscription publishers allow. In the overall balance the situation has nevertheless improved significantly.